Urgensi Pemisahan Peraturan Perundangan Indikasi Geografis Dengan Peraturan Perundangan Merek Di Indonesia - Rinda Fitria Tamara Puteri; Budi Santoso (Notarius, 2023)
AbstractAnalyze the urgency of separating geographic indication regulations from brand regulations in Indonesia. Discusses the urgency of establishing Geographical Indication regulations that are independent of the brand legislation. This type of juridical normative research uses a statutory approach, because this research intends to examine the laws and deficiencies in them. The specification of this research is descriptive analytical. For the type of data used in this study, the type of data used in this study is secondary data. Law Number 20 of 2016 actually requires renewal and the formation of separate regulations that are specific and separate from the trademark law. registering its geographic indication, considering that currently the registration of Geographical Indication is still relatively low due to the complexity of the existing registration process. Renewal of this statutory regulation is also deemed necessary in order to renew and improve the protection of Geographical Indications through the threat of sanctions and penalties which so far still use criminal threats in the trademark law.Keywords : urgency; geographical indication; brand AbstrakAnalisa urgensi pemisahan peraturan perundangan indikasi geografis dengan peraturan merek di indonesia. Membahas mengenai urgensi pembentukan peraturan perundangan Indikasi Geografis yang terlepas dari peraturan perundangan merek. Jenis penelitian yuridis normative dengan pendekatan peraturan perundangan, sebab penelitian ini hendak mengkaji peraturan perundangan serta kekurangan di dalamnya. Spesifikasi penelitian ini adalah deskriptif analitis. Untuk jenis data yang digunakan dalam penelitian ini adalah data sekunder. Undang-Undang Nomor 20 Tahun 2016 sejatinya memerlukan pembaharuan serta pembentukan peraturan tersendiri yang khusus dan terpisah dari undang-undang merek, perlu sebuah peraturan khusus yang memiliki birokrasi pendaftaran yang lebih sederhana, agar dapat mendukung peran aktif masyarakat dalam mendaftarkan indikasi geografisnya, mengingat saat ini pendaftaran Indikasi Geografis masih tergolong rendah akibat rumitnya proses pendaftaran yang ada. Pembaharuan peraturan perundangan ini juga dirasa perlu guna memperbaharui dan meningkatkan perlindungan Indikasi Geografis melalui ancaman sanksi dan pidana yang selama ini masih menggunakan ancaman pidana dalam undang-undang merek.Kata kunci : urgensi; indikasi geografis; merek